Implementation of Reliability Centered Maintenance on Crude Booster Pump - Hafizh, Dzulfikar Ali; Putri, Maya Agustianingrum, ST., Ph.D.; Rizal, D.; Qanita, Adzra (UI Scholars Hub, 2025)
Crude oil booster pump is one of the critical equipment in oil refinery operations. In aging plants that have been operating for more than 25 years, where reliability and maintenance issues on equipment often cause operational disruptions and even unplanned shutdowns. This study aims to develop a structured reliability-centered maintenance (RCM) strategy for crsude oil booster pump systems that is also in line with the principles of asset integrity management system (AIMS). This methodology follows the RCM II approach, starting with system function analysis, failure mode identification, and criticality assessment through Failure Mode, Effect, and Criticality Analysis (FMECA) to determine the Risk Priority Number (RPN) value that looks at the severity, occurrence, and detection rankings to support the priority and selection of maintenance tasks. The results of the study indicate that mechanical seal leakage and bearing wear are the most dominant failure modes, which contribute significantly to operational disruptions. Based on the RCM decision logic, the selected maintenance strategy includes condition monitoring and scheduled restoration tasks. These findings support the integration of RCM results into an asset management framework, which offers practical recommendations to improve pump reliability, reduce corrective maintenance, and support long-term plant availability goals.